Changing histological spectrum of adult nephrotic syndrome in comparison to previous study: single centre analysis - Nath M. Yousuf; Dar M. Ahmad; Wani F. Dawood (International Journal of Research in Medical Sciences, 2023)
Background: Glomerular diseases are an important cause of chronic renal failure in developing countries. The spectrum of diseases causing nephrotic syndrome is changing globally in the last few decades. Methods: Patients in the age group 18-60 years with nephrotic syndrome were consecutively included in the study. Renal biopsies were performed in all patients and were subjected to light microscopy, immunofluorescence (IF) and electron microscopy (EM). Results: 189 patients (67% males) were included in the study. The mean age was 43 years. Primary glomerular diseases accounted for 92.5% of cases while lupus nephritis was the most common secondary glomerular disease. Focal segmental glomerulosclerosis (FSGS) accounted for 28.6% of primary glomerular diseases making it the most common cause of nephrotic syndrome. It was followed by membranous glomerulonephritis (MGN) in 13.2%, membranoproliferative glomerulonephritis in 11.2%, diffuse proliferative glomerulonephritis in 10.6% and minimal change disease in 9.5%. Conclusions: The biopsy diagnosis of FSGS has increased considerably in last few decades and it is now the most common cause of nephrotic syndrome in adults in North India. MGN is the most common lesion in patients over 40 years of age.